Odpowiedź :
Odpowiedź:
[tex]a) f(x) = 3x^{2} + 12x + 19\\ b) f(x) = 2x^2 + 4x\\ c) f(x) = \sqrt{3}x^2 - 4\sqrt{3}x + 4\sqrt{3} + 5[/tex]
Szczegółowe wyjaśnienie:
W zdjęciach
Wzór funkcji kwadratowej możemy również zapisać w postaci kanonicznej, tj. w postaci: f(x) = a(x - p)² + q
a)
f(x) = 3x² + bx + c
W = (-2,7)
W = (p, q)
p = -2, q = 7
a = 3
f(x) = a(x - p)² + q - posta kanoniczna
f(x) = 3(x + 2)² + 7 = 3(x² + 4x + 4) + 7 = 3x² + 12x + 12 + 7
f(x) = 3x² + 12x + 19
b = 12, c = 19
b)
f(x) = 2x² + bx + c
W = (-1, -2)
W = (p, q)
p = -1, q = -2
a = 2
f(x) = a(x - p)² + q - postać kanoniczna
f(x) = 2(x + 1)² - 2 = 2(x² + 2x + 1) -2 = 2x² + 4x + 2 - 2
f(x) = 2x² + 4x + 0
b = 4, c = 0
c)
f(x) = √3 x² + bx + c
W = (2,5)
W = (p, q)
p = 2, q = 5
a = √3
f(x) = a(x - p)² + q - postać kanoniczna
f(x) = √3(x - 2)² + 5 = √3(x² - 4x + 4) + 5 = √3 x² - 4√3 x + 4√3 + 5
f(x) = √3 x² - 4√3 x + 4√3 + 5
b = - 4√3, c = 4√3 + 5